Pengujian Kinerja Blade Taper Menggunakan Turbin Angin Furling Dengan Variasi Kecepatan Angin, Arah Angin, dan Waktu di Pantai Asmara - Oktaviani, Putri Windi Helen; Ramadhana, Dandy; Bintaro, Agung Rahmat; Budi, Aditya Ahmad; Hidayat, Syendi Nur (Jurnal Teknik Terapan, 2025)
With the rapid development of technology and the increasing population growth, energy demand in Indonesia continues to rise. One of the energy potentials that can be harnessed is wind energy, which is an abundant natural resource in Indonesia. The kinetic energy in wind can be used to generate electricity through wind power plants (WPP). This study aims to evaluate the performance of the tapered blades on a furling wind turbine with variations in wind speed and direction at Asmara Beach. The main objective is to determine the effect of wind speed on the performance of tapered blades, analyze the impact of wind direction variations on turbine efficiency and stability, and identify external factors at the location that affect the effectiveness of the furling wind turbine. The results show that the highest recorded power was 9.9968 watts at a wind speed of 4.5 m/s, while the lowest power was recorded at a wind speed of 3.8 m/s, with a power output of 1.516 watts. The generated power was found to fluctuate due to changes in wind speed, causing unstable voltage and current. Wind speed variations have a significant impact on turbine performance, with higher wind speeds generally increasing the power output. However, it is important to note the existence of an optimal wind speed limit to prevent system damage or efficiency degradation. Additionally, wind direction variations also affect turbine stability and efficiency, particularly concerning the furling system's ability to adjust the blade angle to changing wind directions.Keywords: Wind energy, wind turbin, furling wind turbin